Menstrual hygiene management in rural schools of Zambia: a descriptive study of knowledge, experiences and challenges faced by schoolgirls - Joyce Chinyama; Jenala Chipungu; Cheryl Rudd; Mercy Mwale; Lavuun Verstraete; Charity Sikamo; Wilbroad Mutale; Roma Chilengi; Anjali Sharma (BMC, 2019)
Abstract Introduction While in school, girls require an environment that is supportive of menstrual hygiene management (MHM) in order to ensure regular school attendance and participation. Little is known about schoolgirls access to and practice of MHM in rural Zambia. This study explores girls' experiences of MHM in rural schools of Zambia from the perspectives of schoolgirls, schoolboys and community and school-based adults key to MHM for schoolgirls. Methods In July and August 2015, we conducted this qualitative exploratory study in six rural schools of Mumbwa and Rufunsa districts of Zambia. Twelve in-depth interviews (IDIs) and six focus group discussions (FGDs) were conducted among girls ages 14-18 who had begun menstruating. Two FGDs with boys ages 14-18 and 25 key informant interviews were also conducted with teachers, female guardians and traditional leaders to provide the context within which schoolgirls practice MHM. Results Most girls reported learning about menstruation only at menarche and did not know the physiological basis of menstruation. They reported MHM-related challenges, including: use of non-absorbent and uncomfortable menstrual cloth and inadequate provision of sanitary materials, water, hygiene and sanitation facilities (WASH) in schools. In particular, toilets did not have soap and water or doors and locks for privacy and had a bad odor. Girls' school attendance and participation in physical activities was compromised when menstruating due to fear of teasing (especially by boys) and embarrassment from menstrual leakage. Boys said they could tell when girls were menstruating by the smell and their behaviour, for instance, moving less and isolating themselves from their peers. Girls complained of friction burns on their inner thighs during their long journey to school due to chaffing of wet non-absorbent material used to make menstrual cloth. Girls preferred to dispose used menstrual materials in pit latrines and not waste bins for fear that they could be retrieved for witchcraft against them. Though traditional leaders and female guardians played a pivotal role in teaching girls MHM, they have not resolved challenges to MHM among schoolgirls. Conclusion When menstruating, schoolgirls in rural Zambia would rather stay home than be uncomfortable, inactive and embarrassed due to inadequate MHM facilities at school. A friendly and supportive MHM environment that provides education, absorbent sanitary materials and adequate WASH facilities is essential to providing equal opportunity for all girls.